Development of a Prototype Solution for Hearing Problems in Noise in People with Disabilities, Using an Acoustic Beamforming System with a FPGA Card - Sáenz, Fabián (2019)
The study of voice signals is an important issue, since a part of society has hearing impairments. This implementation aims to help people with hearing problems, through enhanced voice; using a microphone array with hemispherical methodology broadband beamforming, which can distinguish signals arriving from different directions. A semi-spherical microphone array adapts better to human anatomy because it captures finer sound field.